MANAJEMEN PELAYANAN BIMBINGAN MANASIK UMRAH PADA PT. AL-BAYAN PERMATA UJAS (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This journal was created with the aim of describing how the management of the and Umrah ritual guidance service is. This type of research is descriptive qualitative, namely to find out how the management of Umrah ritual guidance services at PT. Al-Bayan Gem Ujas. The research is carried out using interview techniques that explore information or in-depth interviews (deph interviews) and observation of active participation models for a particular activity. Descriptive qualitative research is research by collecting data in the form of words, pictures, and not numbers. With an effort to approach the informant concerned as an object of qualitative research (qualitative research). The results of this study indicate that 1) The management of the Umrah ritual guidance service at PT. Al-Bayan Permata Ujas is quite good, by applying POAC management principles (planning, organaizing, actuating, controlling) which is very helpful in the process of managing all activities, 2) The obstacles or obstacles in providing guidance for Umrah rituals at PT. Al- The gems of Ujas Bayan are: 1) Congregants sometimes arrive at the location nothe t on time, 2) there are still pilgrims who are not able and understand Indonesian language, 3) There is still a lack of religious knowledge of the prospective pilgrims, sometimes the congregation at the time of the material does not pay close attention to the material , different educational backgrounds are also one of the obstacles in providing management of Umrah ritual guidance services.